2012
DOI: 10.1175/jcli-d-11-00208.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Intraseasonal Modulation of Tropical Cyclogenesis Environment over the Bay of Bengal during the Extended Summer Monsoon

Abstract: The environmental field of tropical cyclogenesis over the Bay of Bengal is analyzed for the extended summer monsoon season (approximately May-November) using best-track and reanalysis data. Genesis potential index (GPI) is used to assess four possible environmental factors responsible for tropical cyclogenesis: lower-tropospheric absolute vorticity, vertical shear, potential intensity, and midtropospheric relative humidity. The climatological cyclogenesis is active within high GPI in the premonsoon (;May) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 27 publications
2
74
1
Order By: Relevance
“…2d, where the vorticity, vertical wind shear, and mid-level humidity are three leading terms in defining the intra-seasonal GPI ′ . The vorticity and mid-level humidity terms are shown to vary nearly in phase with the cyclogenesis, while the vertical wind shear and PI terms slightly lead, which is similar with Yanase et al (2012).…”
Section: Dominant Process Associated Fniso To Modulate the Ov Genesismentioning
confidence: 54%
See 3 more Smart Citations
“…2d, where the vorticity, vertical wind shear, and mid-level humidity are three leading terms in defining the intra-seasonal GPI ′ . The vorticity and mid-level humidity terms are shown to vary nearly in phase with the cyclogenesis, while the vertical wind shear and PI terms slightly lead, which is similar with Yanase et al (2012).…”
Section: Dominant Process Associated Fniso To Modulate the Ov Genesismentioning
confidence: 54%
“…At seasonal scale, BoB TC activity exhibits a notable bimodal character with peaks in pre-and post-monsoon seasons, in contrast to the single peak distribution in the Pacific and Atlantic basins. This peculiar feature is attributed to the strong modulation by seasonal monsoon circulation (Gray 1968;Yanase et al 2012;Li et al 2013b). It is also identified that BoB TCs are strongly influenced by the intra-seasonal oscillation (ISO) (Camargo et al 2009;Kikuchi and Wang 2010;Yanase et al 2012;Krishnamohan et al 2012).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The favorable hydrographic conditions such as formation of stably stratified thick barrier layer in & Yashvant Das yashvantdas@rediffmail.com 1 the upper ocean that acts as barrier to vertical mixing and entrainment cooling induced by TC's leading to an increase in heat fluxes from the ocean into the atmosphere play a dominant role for the enhanced TC activity over BoB during post monsoon seasons (Sprintall and Tomczak 1992;Sengupta et al 2008;Balaguru et al 2012). TC activity in BoB is strongly modulated by the tropical intraseasonal oscillation (ISO) (Yanase et al 2010(Yanase et al , 2012. The influence of coupled ocean-atmospheric phenomena such as El-Nino, El-Nino Modoki, MJO and Indian Ocean Dipole (IOD) etc.…”
Section: Introductionmentioning
confidence: 99%